1979
DOI: 10.1172/jci109592
|View full text |Cite
|
Sign up to set email alerts
|

Binding of 125I-insulin to the isolated glomeruli of rat kidney.

Abstract: A B S T R A C T To investigate a possible action of insulin on the glomerulus, the binding 1251-insulin to the isolated glomeruli prepared from rat kidney was examined. When incubated at 22°C, '251-insulin binding proceeded with time and reached a steady state at 45 min at which time nonspecific binding was <25% of total binding. A small fraction of '25I-insulin was degraded during incubation. This binding was specific to insulin in that it was inhibited by unlabeled porcine and beef insulins and to a lesser e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
2
14
0
1
Order By: Relevance
“…la). The time course of total binding was similar to that reported with isolated renal plasma membrane preparations [19,20] and in agreement with a recent study by Kurokawa et al [21] in isolated glomeruli. In con trast to total binding, nonspecific binding of l25I-insulin to isolated glomeruli reached a plateau by 10-20 min and amounted to about 25% of the total binding observed.…”
Section: Resultssupporting
confidence: 92%
“…la). The time course of total binding was similar to that reported with isolated renal plasma membrane preparations [19,20] and in agreement with a recent study by Kurokawa et al [21] in isolated glomeruli. In con trast to total binding, nonspecific binding of l25I-insulin to isolated glomeruli reached a plateau by 10-20 min and amounted to about 25% of the total binding observed.…”
Section: Resultssupporting
confidence: 92%
“…Indeed, NOS-2 (inducible) and NOS-3 (endothelial) are both expressed in endothelial and mesangial cells in the glomerular capillaries (16,45), and it has been shown that ANG II-mediated reduction in NO activity can reduce active capillary surface area (3). Insulin receptors are expressed in glomeruli (31) and are known to activate NOS (42). The insulin treatment in the present study could, therefore, have resulted in increased glomerular NO production, leading to mesangial cell relaxation and, therefore, increased K f .…”
Section: Discussionmentioning
confidence: 99%
“…The (26). Alternatively, the glomerular hemodynamic effects of insulin deficiency could reflect altered production of vasoactive hormones within the kidney.…”
Section: Discussionmentioning
confidence: 99%